Factors Influencing Performance, Durability, and Environmental Impact of Hydraulic Structures Using Waste Composite - Ghani, Muhammad Usman; Yonglai, Zheng; Alrasheed, Khaled; Nasim Khan Raja, Babar (Civil Engineering Journal, 2025)
This research explores the crucial elements influencing the impact of hydraulic structures constructed using waste-based composites, emphasizing sustainable material integration in infrastructure. A conceptual model comprising five constructs—Design and Structural Performance, Durability, Environmental Impact, Material Characteristics, and Waste Composites—was established and analyzed utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). Data was combined from 260 construction professionals across the key construction industry. G*Power analysis confirmed the lowest required sample size of 150; the larger sample enhanced statistical robustness. All constructs demonstrated strong reliability, convergent validity, and discriminant validity, with significant path relationships supporting the proposed hypotheses. Material Characteristics (β = 0.568) and Environmental Impact (β = 0.353) emerged as the most influential predictors of hydraulic structure performance. Empirical correlation, cross-loadings, HTMT, and VIF analyses confirmed model stability and construct independence. The results provide precious information for engineers, construction managers, and policymakers aiming to optimize structural integrity and environmental sustainability through the adoption of recycled composite materials. This research contributes to theoretical advancements in sustainable construction and provides practical implications for material selection, policy formulation, and infrastructure design. The study recommends future research on real-time performance monitoring, expanded geographic validation, and inclusion of cost-efficiency and technological integration variables.